Server Based Task Allocation to Reduce Inter-Task Memory Interference in Multicore Systems - Aftab Rashid, Syed (2019)
In multicore systems tasks running on one core may experience inter-task interference from tasks running on other cores. This inter-task interference is due to contention in using shared resources such as caches, system bus and the main memory. In this work, we focus on one of the major sources of cross-core interference in multicore systems, i.e., main memory. The idea is to allocate tasks to cores in a way that the total memory demand of all tasks executing at a time instant t is less than the minimum available memory bandwidth, i.e., DRAM min. The problem is formulated as a server-to-core mapping problem where each server constitute a set of tasks corresponding to an application. As mapping problems in multicore systems are NP-hard, we use different heuristic and meta-heuristic based approaches to find a feasible solution. Results show that our approach can perform well in multicore systems with ≤ 8 processing cores with the memory demand of each server upper bounded by DRAM min/2.